TINJAUAN YURIDIS PENANGANAN TINDAK PIDANA PEMILU MELALUI MEDIA ONLINE DI INDONESIA - Fajar Sidik Duli, Abdul; Sudarto (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2024)
As a special criminal act, election crimes have their own characteristics compared to criminal acts in general. In the technological era, accountability for election crimes cannot be separated from the perpetrators who commit election violations through online media. Potential perpetrators of election violations could be carried out by election organizers, election participants, officials, media, companies, foreign observers or the voting public themselves. The title of this research is a Juridical Review of Handling Election Crimes Through Online Media in Indonesia. The formulation of the problem is: What are the legal arrangements regarding election crimes committed via online media in Indonesia? How is the implementation of Handling of Election Crimes through online media in Indonesia? The research was carried out using a normative juridical approach. The data used is primary, secondary and tertiary data. Data analysis was carried out qualitatively and based on the results of the analysis, conclusions were then drawn using a deductive approach. The conclusion of this research is that the formulation of election crimes in the Election Law still prioritizes election crimes in the implementation of manual or conventional elections. Even though election crimes are not specifically contained in the Election Law, we can find election crimes in the ITE Law which is formulated in 11 criminal acts. Weak enforcement of election crimes through online media is caused by dissatisfaction with Bawaslu's performance in supervising elections. There are at least three problems, namely low digital literacy, limited human resources who understand technology, and minimal election law enforcement regulations in the digital era.